PENANAMAN PENDIDIKAN KARAKTER DALAM PEMBELAJARAN PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN PADA KELAS VIII SMP NEGERI 5 TAMBUSAI TAHUN 2015 - Abdul Putra Ginda Hasibuan (JURNAL PENDIDIKAN ROKANIA, 2016)
The focus of this study is to see how the cultivation of character education in the teaching of Pancasila and citizenship education in SMP Negeri 5 Tambusai. Thestudy design used in the study is a case study (case study) using a qualitative approach. Data collection techniques used through interviews, observation anddocumentation. The data were obtained through two sources, namely primary data and secondary data. The results showed that the first, the implementation ofcharacter education in junior class VIII in particular Tambusai 5 starts by familiarizing the values of discipline, tolerance, responsibility and honesty of students. Second, in molding the character of students, found in this study that not only in the delivery of learning in the classroom. But it can be done through self-development and other activities are still the guidance of SMP Negeri 5 Tambusai.